MODEL DINAMIK PADA SISTEM PROSES PENGOLAHAN AIR LIMBAH KOLAM STABILISASI FAKULTATIF - Dian Huliyun Rahmania (Jurnal Matematika, 2015)
MODEL DINAMIK PADA SISTEM PROSES PENGOLAHAN AIR LIMBAH KOLAM STABILISASI FAKULTATIF                                                           Dian Huliyun Rahmania1, Sunarsih2, Nikken Prima Puspita31,2,3Program Studi Matematika FSM Universitas DiponegoroJl. Prof. H. Soedarto, S.H. Tembalang Semarang dianhuliyun@gmail.comsunarsihmat@gmail.com ABSTRACT. Domestic wastewater is wastewater generated from a household activities that can pollute the environment. If this wastewater pollution did not dealt seriously can cause several problems. To overcome these problems, the wastewater needs to undergo treatment processing in advance. One of the treatment processing system is using units Wastewater Treatment Plant (WWTP). The purpose of this thesis is to contruct dynamic model of wastewater treatment on facultative stabilization ponds in simulating these model and then validate it. The result of model simulation shows that there is an error rate of <10% by comparing model and observation data toward algae, bacteria, dissolved oxygen, and substrate. Model is done numerically using euler method. Keywords: Domestic Wastewater, Facultative Stabilization Ponds, Dynamic Modeling, Euler Method.